Ornamental Variety of Garuda and Wilmana on Padmasana Architecture at Kahyangan Jagat Temple in Bali, Indonesia - Dwijendra, Ngakan Ketut Acwin; Idedhyana, Ida Bagus; Putu Sueca, Ngakan; Wirawibawa, Ida Bagus (International Journal of Engineering and Emerging Technology; Vol 5 No 1 (2020): January - June, 2020)
Garuda was known in prehistoric India, where his paintings were found in the Harappa (Sindhu River valley), then spread to all corners of the world affected by Indian civilization. Its head, beak and claws are eagles, the light of the gods shining from its body. While Wilmana as a picture of a space vehicle that moves beyond the speed of thought. Wilmana is also a worldwide character, presented in the world of the internet, film and games. Padmasana architecture is a sacred building as a place/position of God, on the back is often carved by the two kinds of decoration. This research about ornamental variety is research in the context of traditional architecture, as an exploration of building concepts that have been developed in the past and are useful to apply to contemporary architecture. This study aims to re-express the meaning of Garuda and Wilmana and how they are placed on Padmasana architecture. The steps taken are to record the Padmasana in the Kahyangan Jagat Temple in Bali, followed by comparing the use of these two types of decoration on each Padmasana . The next step is to interpret the meaning by connecting the object with its past (expanding the horizon of the researcher). The results of the study show that the use of Garuda and Wilmana decoration in the Padmasana architecture is not a necessity. The use of Garuda points to the message that humans must try to free themselves from the bondage of worldly passions. While the use of Wilmana refers to the sky vehicle that carries passengers, both Giant and Dewata to the place they want. Both are symbolic decoration types, have the same position, placed on the body behind the padmasana . The position of the two becomes different if applied together, Garuda is placed in a position above Wilmana , because only a soul that has been freed from worldly slavery can ride Garuda.